TRANSFORMATIONAL PROCESSES OF NATIONAL IDENTITY IN THE CONTEXT OF THE INFORMATION SOCIETY AND VIRTUAL SPACE - Bekzod Muhammadiyev (Modern American Journals, 2025)
In the context of rapid digitalization and the expansion of the information society, virtual space has become a significant factor influencing the transformation of national identity. This article examines the transformational processes of understanding and perceiving national selfhood under the conditions of an information-based society and virtual environments. Special attention is paid to the role of digital communication platforms, social networks, and virtual communities in reshaping national consciousness, cultural values, and collective memory. The study analyzes both the constructive and disruptive effects of virtual space on national identity, highlighting the opportunities for preserving national values as well as the risks of cultural homogenization and identity fragmentation. Using socio-philosophical and interdisciplinary approaches, the article reveals how national self-awareness is reinterpreted and reconstructed within virtual realities, emphasizing the importance of developing effective cultural and informational strategies to strengthen national identity in the digital age.
Keywords: Information society, virtual space, national identity, self-awareness, digital culture, virtual reality, globalization, cultural transformation.